2020
DOI: 10.32479/ijeep.9822
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Fluctuations and Exchange Rate in Selected Sub-Saharan Africa Countries: A Vector Error Correction Model Approach

Abstract: This study employs the Johansen cointegration and the vector error correction model (VECM) to assess the dynamic relationship that exists between oil price fluctuations and the real exchange rate in selected Sub-Saharan Africa countries from January 2004 to December 2017. The result of the monthly data analysis provides evidence to support a cointegration between oil prices and the real exchange rate in sub-Saharan oil dependent nations. The results of the study established a long-run equilibrium connection be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The fluctuations of crude oil price directly transmit into economic output through real exchange rate. A related study by Ehikioya et al (2020) where Johansen Cointegration techniques were used to explore the relationship between prices of crude oil and real exchange rate in selected sub-Saharan African countries from 2004 to 2017. The results obtained from the study showed that fluctuations in the prices of crude oil predicted real exchange rates movement in countries like Angola, Congo, Equatorial Guinea, Nigeria and Gabon.…”
Section: Review Of Past Studies On Crude Oil Price and Real Exchange ...mentioning
confidence: 99%
“…The fluctuations of crude oil price directly transmit into economic output through real exchange rate. A related study by Ehikioya et al (2020) where Johansen Cointegration techniques were used to explore the relationship between prices of crude oil and real exchange rate in selected sub-Saharan African countries from 2004 to 2017. The results obtained from the study showed that fluctuations in the prices of crude oil predicted real exchange rates movement in countries like Angola, Congo, Equatorial Guinea, Nigeria and Gabon.…”
Section: Review Of Past Studies On Crude Oil Price and Real Exchange ...mentioning
confidence: 99%
“…To preserve profitability in response, businesses may use cost-cutting strategies, such as lowering labor costs through layoffs or hiring freezes (Ghosh, 2021). Furthermore, higher oil prices may prompt firms to invest in energysaving technologies or alternative energy sources, which can lead to structural changes in the labor market, such as shifts in employment from energy-intensive industries to cleaner and more sustainable sectors (Ehikioya et al, 2020). Conversely, when oil prices decline, businesses may experience cost savings, which can translate into higher profit margins and increased investment in expansion and hiring (Elder & Payne, 2023).…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Vochozka et al (2020) investigated the impact of international crude oil prices on the EUR/USD exchange rate by using neural networks and found that Brent crude oil prices significantly impact the Euro-USD exchange rate and therefore can be predicted accurately. Ehikioya et al (2020) investigated the relationship between oil price fluctuations and real exchange rates in sub-Saharan African countries on the data from 2004 to 2017 by employing the Johnson cointegration and vector error correction model. The authors found a dynamic relationship between oil prices and the exchange rate in sub-Saharan countries, Nigeria, Angola, Equatorial Guinea, Gabon, and the Republic of Congo.…”
Section: Association Between Oil Prices and Exchange Ratesmentioning
confidence: 99%